Cytology‐based screening for anal intraepithelial neoplasia in women with a history of cervical intraepithelial neoplasia or cancer. Issue 2 (1st October 2020) - Wohlmuth, Christoph; Ghorab, Zeina; Shier, Michael; Tinmouth, Jill; Salit, Irving E.; Covens, Allan; Zhang, Liying; Vicus, Danielle
Abstract : Background: High‐risk human papillomavirus (HPV) has been identified in the pathogenesis of anal cancer. The purpose of this study was to assess the prevalence of abnormal anal cytology and HPV in women aged ≥40 years who have a history of high‐grade cervical squamous intraepithelial lesion (SIL) or cancer and to estimate the prevalence of anal intraepithelial neoplasia (AIN) using cytology as the primary screening modality. Methods: Women who had a history of high‐grade cervical SIL or cancer and were ≥40 years of age were included in this prospective study. Anal cytology with HPV‐DNA testing was performed. All patients with abnormal anal cytology were referred for high‐resolution anoscopy (HRA), and abnormal lesions were biopsied and treated if pathologically confirmed. Abnormal anal cytology correlated with HPV status, HRA findings, and clinical and demographic characteristics. Results: A total of 317 women completed the study. Of these, 96 (30.3%) had abnormal anal cytology (high‐grade SIL, 12.5%; low‐grade SIL, 19.8%; atypical squamous cells, cannot exclude high‐grade SIL, 6.3%; atypical squamous cells of undetermined significance, 61.5%) and 101 (31.9%) were HPV‐DNA–positive. There was a significant association between abnormal cytology results and the presence of high‐risk HPV. Of the 96 patients with abnormal cytology, 30 (31.3%) had biopsy‐proven AIN on HRA, representing 9.5% of the total patient cohort; of these, 10 (33.3%) had low‐grade AIN and 20 (66.7%) had high‐grade AIN. Older age and smoking were significant risk factors for abnormal anal cytology. Conclusion: Women aged ≥40 years with a history of high‐grade cervical SIL or cancer have a high rate of AIN. Screening for anal cancer may therefore be considered in this patient population. The optimal screening approach should be addressed in future studies. Abstract : Almost one‐third of women with a history of cervical high‐grade squamous intraepithelial lesion and cervical cancer have abnormal anal cytology. Of these, 30% have biopsy‐proven anal intraepithelial neoplasia.